Analisis Sentimen Masyarakat terhadap Sistem Pembelajaran Online selama Pandemi Covid-19 berdasarkan dari Twitter menggunakan Metode Naive Bayes - Moch Bima Prakoso; Imam Cholissodin; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Twitter is one of the most popular social media among young people in Indonesia. In Twitter social media, there is a tweet feature that is commonly used by users to express their experiences or provide criticism on an event that is currently being discussed. At the beginning of March 2020, Indonesia was shaken by the entry of the corona virus or commonly known as Covid-19. Previously the virus had spread in parts of the world, especially in the Asian continent. The impact of Covid-19 in Indonesia is very large, especially in the corporate and education sectors. In the corporate sector, many companies are experiencing a decline in income and are threatened with bankruptcy, not much different from the education sector also experiencing various problems, to prevent the spread of the virus the government has closed teaching and learning activities. Then the government provides a policy to conduct online or online teaching and learning activities. In this solution, there are still pros and cons among the community. Therefore, the data grouping of community tweets related to the online learning system during the pandemic was carried out, using the Naive Bayes method of community tweets. This test was carried out using Cross Validation and Confusion Matrix to obtain accuracy results. In this study, accuracy results were obtained with 10 trials with an average value of 0.59 Accuracy, 0.61 Precision, 0.60 Recall, 0.58 F-Measure.